1973
DOI: 10.1037/h0034497
|View full text |Cite
|
Sign up to set email alerts
|

The effects of denial of early mother-infant interaction on maternal self-confidence.

Abstract: Attitudes of self-confidence in caring for their infants were measured using a paired comparison questionnaire for two groups of mothers: a separation group of 21 mothers denied physical interaction with their premature infants in the first weeks following birth and a contact group of 22 mothers allowed to care for their premature infants in the hospital nursery during this period. Separation resulted in lower self-confidence for primiparous mothers (p < .01) but not for multiparous mothers. Comparing mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 7 publications
4
32
1
Order By: Relevance
“…The infants are usually in need of medical assistance in order to meet the demands of the extra-uterine world to which they are not yet adapted. The parents are in most cases adversely affected by this situation, which may lead to guilt feelings, lack of self-confidence and considerable anxiety, especially when the infant is very sick and the parents fear the baby will die (Affleck ef al., 1990;Jeffcoate et al, 1979;Seashore et al, 1973). The timing of birth and experiences during the neonatal period are not in line with the expectations, and the parents have had limited opportunity to get acquainted with their baby during the hospital stay, making it more difficult to establish a relationship with the baby.…”
Section: The Hospital Periodmentioning
confidence: 99%
“…The infants are usually in need of medical assistance in order to meet the demands of the extra-uterine world to which they are not yet adapted. The parents are in most cases adversely affected by this situation, which may lead to guilt feelings, lack of self-confidence and considerable anxiety, especially when the infant is very sick and the parents fear the baby will die (Affleck ef al., 1990;Jeffcoate et al, 1979;Seashore et al, 1973). The timing of birth and experiences during the neonatal period are not in line with the expectations, and the parents have had limited opportunity to get acquainted with their baby during the hospital stay, making it more difficult to establish a relationship with the baby.…”
Section: The Hospital Periodmentioning
confidence: 99%
“…Mercer (1985) has suggested that a woman's concept of "being a good mother" relates to the thriving status of her infant. Mothers who have been separated from their preterm infants during the postpartum period have been found to report lower feelings of self-confidence than mothers who had early contact with their preterm infants (Seashore, Leifer, Barnett, & Leiderman, 1973). Additional research has fourid that reduced maternal self-confidence during the neonatal period may be enhanced by extended postpartum contact (Sostek, Scanlon, & Abramson, 1982).…”
Section: Discussionmentioning
confidence: 97%
“…A high-risk and disabled infant mobilizes a number of emotional and psychological reactions to parents. Parents have been found to experience feelings of guilt [11,12], to manifest a high level of defensive attribution and self-blame [13], to feel a deep sense of failure [14], and to express grief and mourning responses [15,16] accompanied by depression [17]. Feelings of love and invest ment are often withheld to protect the parent from grief, in case the infant dies [18,19].…”
Section: Pre-and Perinatal Factorsmentioning
confidence: 99%